Analisis Perbandingan Kepailitan Harta Peninggalan Antara Hukum Indonesia dan Malaysia - Albert Sintong Limbong; Handar Subhandi Bakhtiar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article discusses the comparative law between Indonesia and Malaysia regarding bankruptcy of inheritance left by a deceased testator. In Indonesia, Bankruptcy of Inheritance and Responsibility of Heirs Based on the